Factors Influencing the Acceptance of Mobile Learning in K-12 Education in Saudi Arabia: Towards a Shift in the Saudi Education System vis-à-vis Saudi 2030 Vision - Alturise, Fahad; Alshmrany, Sami; Alkhalifah, Tamim; Alkhalaf, Salem (International Journal of Interactive Mobile Technologies (iJIM), 2022)
The Saudi Arabian government is committed to updating and improving its education system. Thus, in March 2017, a project was declared to convert the existing book-based methodology to modern, mobile technology in the K-12 education space by 2021. As part of this process, a deep-dive literature review of student acceptance of mobile learning confirmed that there was limited research into what elements had an effect on how much students were likely to accept learning with mobile applications in the five to 18-year-old demographic of K-12. The conclusion of the literature review was that the Saudi Arabian Education Ministry must acquire an understanding of these elements in order to strategize the implementation of the new technology. This study approached high school students, aged 16 – 18, in Saudi Arabia, to examine the elements which would influence their acceptance of mobile learning technology. The research consolidated known elements of education, namely learning self-management, system quality, and hedonic motivation with the Unified Theory of Acceptance and Use of Technology (UTAUT) to create a significant theoretical model for the new technology in a high school setting. Conclusions were drawn that societal influence did not affect the student’s approach to mobile learning, but that learning self-management, the expectancy of effort and performance, hedonic motivation and the quality of the system did affect the acceptance behaviour of the students. It was also noted that gender was not a significant factor in the study